Truncated tetragonal bipyramidal anatase nanocrystals formed without use of capping agents from the supercritical drying of a TiO2 sol. Issue 1 (1st December 2015) - Tobaldi, D. M.; Pullar, R. C.; Durães, L.; Matias, T.; Seabra, M. P.; Labrincha, J. A.
Abstract : Titanium dioxide (TiO2 ) nanoparticles are extremely attractive materials for numerous applications, especially in the anatase form. Abstract : Titanium dioxide (TiO2 ) nanoparticles are extremely attractive materials for numerous applications, especially in the anatase form. We have made these shaped, <10 nm anatase nanoparticles (NPs) via the supercritical (SC) drying of a titania sol, made by a "green" aqueous sol–gel nanosynthesis route. The SC drying was carried out in alcohol at 255–260 °C, and no further heating or processing of the NPs was required. The true phase composition (crystalline and amorphous phases) and the microstructure of the NPs was thoroughly characterised by the advanced X-ray methods, such as Rietveld-reference intensity ratio (RIR) and the whole powder pattern modelling (WPPM) technique, and HR-TEM analysis. Furthermore, the NPs were also characterised by Raman, FT-IR and optical spectroscopy. These anatase NPs showed themselves to exhibit a truncated tetragonal bipyramidal shape, exposing the 101 (side) and 001 (top) faces. They had a euhedral crystal habit, with sharply defined and easily recognised faces, and were very homogeneous and monodisperse in both shape and size. The photocatalytic activity (PCA) of the samples was assessed in gas–solid phase by monitoring the degradation of nitrogen oxides (NO x ), a major atmospheric pollutant. Results showed that the particular shape of these anatase NPs played a key role in their photocatalytic behaviour. In fact, these truncated tetragonal bipyramidal nanocrystals exhibited an enhanced photocatalytic activity, double that of spherical anatase NPs of a similar size reported previously by the authors. This was attributed to the exposure of mainly the 101 and, to a lesser extent, 001 crystal faces, which are more reactive under photocatalysis for redox reactions.